1984
DOI: 10.2307/3226468
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Antennal Sense Organs of Nasonia vitripennis (Hymenoptera: Pteromalidae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
43
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 12 publications
(19 reference statements)
11
43
1
Order By: Relevance
“…The antenna of E. guadeloupae consists of three basic parts, scape with radicula, pedicel, and flagellum (Chapman, 1998;Isidoro et al, 1996). Eight morphologically different types of sensilla were found on the female antennae of E. guadeloupae, similar to those described in other closely related aphelinidae species, such as Encarsia asterobemisiae (Viggiani 1982), Encarsia mineoi (Viggiani and Mazzone, 1980;Viggiani, 1982), Encarsia amicula (Wang and Huang, 2007), Aphytis melinus De Bach (Romero and Heraty, 2010) and other parasitic Hymenoptera (Wibel et al, 1984;Navasaro and Elzen, 1991;Cônsoli et al, 1999;Ochieng et al, 2000;Roux et al, 2005;Bourdais et al, 2006;Gao et al, 2007;Dweck, 2009). The different terminologies were used to describe the same type of antennal sensilla, so we should note it in the study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The antenna of E. guadeloupae consists of three basic parts, scape with radicula, pedicel, and flagellum (Chapman, 1998;Isidoro et al, 1996). Eight morphologically different types of sensilla were found on the female antennae of E. guadeloupae, similar to those described in other closely related aphelinidae species, such as Encarsia asterobemisiae (Viggiani 1982), Encarsia mineoi (Viggiani and Mazzone, 1980;Viggiani, 1982), Encarsia amicula (Wang and Huang, 2007), Aphytis melinus De Bach (Romero and Heraty, 2010) and other parasitic Hymenoptera (Wibel et al, 1984;Navasaro and Elzen, 1991;Cônsoli et al, 1999;Ochieng et al, 2000;Roux et al, 2005;Bourdais et al, 2006;Gao et al, 2007;Dweck, 2009). The different terminologies were used to describe the same type of antennal sensilla, so we should note it in the study.…”
Section: Discussionmentioning
confidence: 85%
“…And above all, they possess a typical bulbous peg with longitudinal grooves. The main functional significance of BCPS is related with the olfaction for numerous pores in the furrows on the bulbous distal peg (van Baaren et al, 1996;Steinbrecht, 1997;Keil, 1999;Bleeker et al, 2004), or as hygro-, thermo-and mechanoreceptors (Wibel et al, 1984;Wcislo, 1995;Pettersson et al, 2001). They could involve a bi-modal function as chemo-and thermoreceptors (Isidoro et al, 1996(Isidoro et al, , 1999.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have characterized the antennal sensilla of various species of parasitic wasps using electron microscopic techniques (Norton and Vinson, 1974; Wibel et al, 1984;Navasaro and Elzen, 1991;Olson and Andow, 1993;van Baaren et al, 1996;Isidoro et al, 1996;Amornsak et al, 1998;Ochieng et al, 2000;Pettersson et al, 2001;Bleeker et al, 2004). Many of these studies reported strong sexual dimorphism in structure and types of antenna1 sensilla (Wibel et al, 1984;Navasaro and Elzen, 1991;Amornsak et al, 1998;Bleeker et al, 2004), whereas other authors reported little or no distinct sexual differences in the antennal sensory system (Ochieng et al, 2000;Pettersson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In general, a great number of ST1 occur on the males and females. The multiporous sensilla trichoidea have previously been described with different names including multiporous sensilla trichoidea with wall pores (Wible et al, 1984;Petterson et al, 2001;Ryan 2002;Onagbola and Fadamiro, 2007;Bleeker et al, 2004;Onagbola and Fadamiro, 2007). In general antennal sensilla trichoidea are presumed to function as olfactory receptors in many insects (Steinbreacht, 1987(Steinbreacht, , 1997Bleeker et al, 2004), and electrophysiological studies have confirmed sex pheromone receptor function for the trichoid sensilla of Neodiprion sertifer Geoffory (Hymenoptera: Diprionidae) (Hansson et al, 1991).…”
Section: Discussionmentioning
confidence: 99%